Information and psychological impact in the context of strategic communications paradigm - Alexander G. Karayani; Yuliya M. Karayani (Национальный психологический журнал, 2021)
Background. The change in the paradigm of information-psychological confrontation caused changes in the content and architectonics of information-psychological impact, and determined the new trends in the forms of their practical use. Identifying the features of information and psychological impact in the context of strategic communications will make it possible to ensure the information and psychological security of person and society in a more targeted way. Objective. To identify the types, features and trends in the application of information-psychological impact in the context of the strategic communications paradigm. Results. The study reveals the essence of strategic communications as a paradigm of information-psychological confrontation. It analyzes architectonics and content of the main types of information and psychological impact. The study also discusses the main trends in the development of methods and forms of information and psychological impact. Conclusions. The context of strategic communications extends the understanding of information and psychological impacts. It is advisable to consider it as a deliberate dissemination (promotion, blocking and/or selection) of information, interaction and movement between participants in the communication process. Strategic communications use impact methods related to “hard power” meta-strategies based on coercion and “soft power” using attraction technologies. The implementation of these meta-strategies is accompanied by trends reflecting the transition from influence on the military enemy to impact on civilians; from “hard” to “soft” methods of exposure; from monological forms (dissemination of information, influence) to dialogical forms (communication); from an open invasion of consciousness and human behavior to more hidden forms of influence; from tactical forms designed for immediate effect to strategic forms aimed at a distant outcome; from monotype forms of influence to diverse, difficult, complex ones. To ensure the information-psychological security of the person and society, knowledge and consideration of the peculiarities of information and psychological impact are necessary within the framework of the current paradigm of information-psychological confrontation.